Targeting : Poor and Vulnerable Households in Indonesia - World Bank (World Bank, Jakarta, 2017)
Indonesia has experienced strong economic growth over the last forty years. At the same time, the proportion of Indonesians living below the poverty line has fallen dramatically. Nonetheless, around 12 percent of Indonesians remain in poverty and another 30 percent remain highly vulnerable to falling into poverty in any given year. In addition, Indonesia has experienced a number of crises in the last two decades, and such shocks are likely to continue in the future in an increasingly integrated global economy. Over the last fifteen years the Government has been developing social assistance programs designed to promote the poor out of poverty and protect poor and vulnerable households from both individual and more widespread shocks. The coverage, design and implementation of these programs continue to be improved as social protection in Indonesia matures, but a number of issues remain. One of the most important, and difficult, is how these programs can accurately target households who need those most. The challenge is to develop a targeting approach which includes most of the poor and vulnerable while minimizing leakage to the rich. At the same time, the system must be feasible, affordable, and accepted and used by all. Furthermore, identifying which households are poor is a difficult task in any developing country, but is particularly so in Indonesia, which has a very large population, a high degree of geographic dispersion, decentralization of much budgetary and operational governance, and frequent entry and exit of households into and from poverty. This evidence-based report builds in part on innovative research done collaboratively with the Government of Indonesia. In this respect Indonesia is contributing to the frontier of global knowledge on targeting, while also drawing on the experience of other countries. Moving from a thorough assessment of the current effectiveness of targeting in Indonesia, the report contains practical and detailed recommendations for the future. In particular, a National Targeting System is proposed, which envisages developing a single registry of potential beneficiaries to target social assistance to the right households, resulting in more accurate and cost-effective targeting outcomes, and ultimately stronger program impacts.